Socio-environmental strategy: integration of pisciculture with fertigated fruit culture in Vale do Jaguari/RS, Brazil (Revista Brasileira de Contabilidade e Gestão, 2013)
This paper proposes a new integrated production strategy for fish farming with drip-fertigated fruit farming, consorting 75 family farmers in Vale do Jaguari, in Rio Grande do Sul, Brazil. For this, an innovative Social Technology is proposed, not yet registered in the Brazilian heritage; at least, with respect to its demonstration and multiplier effect, the initial subsidy and support to farmers and the pre-incubation of start-ups. The greatest expected impacts will be reflected in the results of the professional qualification of at least 250 young people who will now have objective elements to abandon their predisposition to imminent emigration. The impacts on the environment and ecology will be substantial. The multiple use of water will be practiced to save it and make its exploitation more efficient. Biofertilized water will largely replace chemical fertilization. And the damage caused by the recurring droughts that have plagued and impoverished the region for years will be minimized.
Keywords: social and environmental strategy; social technology; sustainable regional development; agribusiness